The Influence of Influencer Marketing on Instagram towards Secondate Brand Awareness in Jakarta - Lie, Shearent; Sitinjak, Tony (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
This study explores the impact of Influencer Marketing on Instagram on Secondate brand awareness in Jakarta. Drawing on Influencer Marketing and Brand Awareness theories, the research employs a quantitative approach with 145 active Instagram users who follow Titan Tyra, an influencer associated with the Secondate brand. Using simple regression analysis, the study finds that the model effectively predicts brand awareness. The t-test indicates a significance value below 0.05, supporting the hypothesis that influencer marketing significantly influences Secondate brand awareness. The conclusion highlights a positive correlation between Influencer Marketing and Brand Awareness, emphasizing the importance of this strategy for companies in Jakarta seeking to enhance their brand presence on Instagram.